Determination of key economic indicators and digital metrics for project portfolio management - Kostenko, Denys; Storozhuk , Oleksandr (Ways to Improve Construction Efficiency, 2024)
The article is devoted to identifying key economic indicators and digital metrics required for effective management of construction project portfolios in the context of post-war recovery and the dynamic digital transformation of the industry. The authors substantiate the need to move away from traditional linear-functional management models that were shaped in stable economic conditions and are unable to match the pace of contemporary market changes. The paper systematizes the experience of classical business process reengineering (Hammer & Champy, Davenport) and leading international studies, including the HTO framework, the integration of artificial intelligence and robotic process automation (AI/RPA), as well as the use of process mining for the analysis of “live” processes. It is shown that the implementation of BIM, ERP, and IPD platforms, combined with big-data analytics and digital twins, makes it possible to reduce costs, accelerate project execution, and increase the transparency of financial flows. Particular attention is paid to the evolution of service-oriented public–private partnership models, especially build–operate–transfer, which combine financial attractiveness for investors with the long-term sustainability of infrastructure assets. The authors propose a comprehensive set of indicators for evaluating the effectiveness of such projects: financial and economic (IRR, NPV, DSCR), operational (availability, efficiency of operating costs), service (SLA compliance, innovativeness of solutions), socio-environmental (CO₂ emissions, energy efficiency, community impact), and institutional (regulatory stability, quality of risk allocation). They emphasize that the strategic integration of innovation, digital technologies, and ESG principles creates a foundation for the sustainable development of the construction industry, ensures flexibility in responding to the challenges of the post-war economy, and provides a basis for long-term partnerships between the state, business, and society.